Substituting spent copper slag as a replacement for sand as fill material in land reclamation projects - Ng, Xiang Hui. (2012)
The lack of waste landfill used for waste disposal and the increasing cost of fill materials used for land reclamation projects in Singapore has led to the study on the suitability of using spent copper slag, a by-product of removing rust and marine deposit on ships, as the primary fill material for construction and land reclamation in Singapore.